Examination of behavioral flexibility and function of severe challenging behavior in individuals with autism and intellectual disability. (2nd July 2016) - Liddon, Clare J.; Zarcone, Jennifer R.; Pisman, Maegan; Rooker, Griffin W.
Abstract : Objectives : Behavioral flexibility may be an important aspect of the occurrence of challenging behavior in individuals with autism and intellectual disability (ID). The primary purpose of the current study was to examine the scores on the Behavioral Flexibility Rating Scale-Revised (BFRS-R) across two groups of individuals with autism: those with ID (AID) and those without ID (A). These scores were then compared to the outcome of each participant's functional analysis. In addition, we evaluated the relationship between these scores and reported adaptive behavior (Vineland Adaptive Behavior Scale) within each group. Methods : The BFRS-R is a survey measure of the degree of an individual's behavioral inflexibility. Specifically, the BFRS-R identifies those contexts in which challenging behavior is most likely to occur. In the current study, the BFRS-R, functional analysis of challenging behavior outcome, and Vineland II scores were correlated using a Mann–Whitney test for 110 individuals admitted to a specialized inpatient unit. Results : There was a significant difference ( p  < .05) between the BFRS-R scores of the A group and the AID group. The A group had slightly higher mean scores (18.3 compared to 15.3), and these individuals were more likely to have challenging behavior maintained by automatic reinforcement. Within this group, an automatic function was most likely if the BFRS-R score was above 16. Individuals in the AID group were more likely to have challenging behavior maintained by access to tangible items and activities. Consistent with previous research, higher scores on the BFRS-R were correlated with a higher Adaptive Behavior composite score on the Vineland for both groups. Conclusions: The BFRS may help inform the functional assessment process so that specific conditions can be evaluated. Also, we were surprised to find that high adaptive scores did not necessarily mean that the individuals with autism had more behavioral flexibility. In fact they had less.